Ø¯ÙØ§ÙØ¹ Ø§ÙØ·ÙØ§Ø¨ ÙÙ ØªØ¹ÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© Ù Ø¯ÙØ± Ø§ÙÙØ¹ÙÙ ÙÙ ØªØ±ÙÙØªÙØ§ - Rusady, Achmad Tito (IZDIHAR, 2018)
Learner of Arabic language still finds many difficulties in learning Arabic. It may be caused by motivation. The stronger motivation, the smaller difficulties and the weaker motivation, the greater difficulties. Many students can get their will and success no matter how many difficulties are, with strong motivation as the basis for success. Motivation is a manifestation of studentsâ knowledge of the goals in work either by their own attempt or by instructing the teacher as their defensive role in promoting motivation.